Thymus transplantation restores the repertoires of forkhead box protein 3 (FoxP3)+ and FoxP3− T cells in complete DiGeorge anomaly. (6th June 2013) - Chinn, I. K.; Milner, J. D.; Scheinberg, P.; Douek, D. C.; Markert, M. L.
Summary The development of T cells with a regulatory phenotype after thymus transplantation has not been examined previously in complete DiGeorge anomaly (cDGA). Seven athymic infants with cDGA and non‐maternal pretransplantation T cell clones were assessed. Pretransplantation forkhead box protein 3 (Foxp3)+ T cells were detected in five of the subjects. Two subjects were studied in greater depth. T cell receptor variable β chain (TCR‐Vβ) expression was assessed by flow cytometry. In both subjects, pretransplantation FoxP3+ and total CD4+ T cells showed restricted TCR‐Vβ expression. The development of naive T cells and diverse CD4+ TCR‐Vβ repertoires following thymic transplantation indicated successful thymopoiesis from the thymic tissue grafts. Infants with atypical cDGA develop rashes and autoimmune phenomena before transplantation, requiring treatment with immunosuppression, which was discontinued successfully subsequent to the observed thymopoiesis. Post‐transplantation, diverse TCR‐Vβ family expression was also observed in FoxP3+ CD4+ T cells. Interestingly, the percentages of each of the TCR‐Vβ families expressed on FoxP3+ and total CD4+ T cells differed significantly between these T lymphocyte subpopulations before transplantation. By 16 months post‐transplantation, however, the percentages of expression of each TCR‐Vβ family became significantly similar between FoxP3+ and total CD4+ T cells. Sequencing of TCRBV DNA confirmed the presence of clonally amplified pretransplantation FoxP3+ and FoxP3− T cells. After thymus transplantation, increased polyclonality was observed for both FoxP3+ and FoxP3− cells, and pretransplantation FoxP3+ and FoxP3− clonotypes essentially disappeared. Thus, post‐transplantation thymic function was associated with the development of a diverse repertoire of FoxP3+ T cells in cDGA, corresponding with immunological and clinical recovery.